2021
DOI: 10.3390/bios11120511
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Fabrication of Stimuli-Responsive Chitosan-Platinum Brushes for Listeria monocytogenes Detection

Abstract: Bacterial contamination in food-processing facilities is a critical issue that leads to outbreaks compromising the integrity of the food supply and public health. We developed a label-free and rapid electrochemical biosensor for Listeria monocytogenes detection using a new one-step simultaneous sonoelectrodeposition of platinum and chitosan (CHI/Pt) to create a biomimetic nanostructure that actuates under pH changes. The XPS analysis shows the effective co-deposition of chitosan and platinum on the electrode s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“… (A) The novel principles behind AuNPs optical biosensing and the schematic representation of DNA sandwich hybridization targeting ttrRSBCA locus of Salmonella spp. ( Quintela et al, 2019 ); (B) Illustration of the white light reflectance spectroscopy (WLRS) optical setup and sensing and sensing principle ( Angelopoulou et al, 2021 ); (C) Schematic diagram of electrochemical detection of E. coli O157:H7 by gold nanoparticle-catalyzed silver enhancement at porous pseudo-carbon paste electrode ( Xu et al, 2012 ); (D) Fabrication, biofunctionalization, and sensing scheme of CHI/Pt aptasensor ( Oliveira et al, 2021 ). …”
Section: Biosensor Detection Technologymentioning
confidence: 99%
See 2 more Smart Citations
“… (A) The novel principles behind AuNPs optical biosensing and the schematic representation of DNA sandwich hybridization targeting ttrRSBCA locus of Salmonella spp. ( Quintela et al, 2019 ); (B) Illustration of the white light reflectance spectroscopy (WLRS) optical setup and sensing and sensing principle ( Angelopoulou et al, 2021 ); (C) Schematic diagram of electrochemical detection of E. coli O157:H7 by gold nanoparticle-catalyzed silver enhancement at porous pseudo-carbon paste electrode ( Xu et al, 2012 ); (D) Fabrication, biofunctionalization, and sensing scheme of CHI/Pt aptasensor ( Oliveira et al, 2021 ). …”
Section: Biosensor Detection Technologymentioning
confidence: 99%
“…The target analyte can be quantified by monitoring the change of these signals. Oliveira et al (2021) developed a label-free and rapid electrochemical biosensor for LM detection using a new one-step simultaneous sonoelectrodeposition of platinum and chitosan (CHI/Pt) to create a biomimetic nanostructure that actuates under pH changes ( Figure 5D ). Actuation led to improved LM detection with a low limit of detection (33 CFU/10 ml in chicken broth).…”
Section: Biosensor Detection Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of PON devices include detection of exposed proteins on pathogens, (e.g., SARS-CoV-2 spike protein [ 5 , 6 ]), detection of protein biomarkers [ 7 , 8 ] (e.g., cancers, cardiac diseases, autoimmune diseases, and acute events), and identification of plant pathogens in the food system (e.g., Listeria spp. invasion proteins [ 9 , 10 ]). In this special issue of Biosensors, we build on the concept of context-awareness through establishment of CADS: Context-Aware Diagnostic Specificity, an application specifically focused on diagnostics.…”
Section: Commentarymentioning
confidence: 99%
“…Comprehensive reviews on aptamer-based technologies for foodborne pathogen detection summarize recent developments in optical and electrochemical biosensors (i.e., aptasensors) 24 , 27 , 28 , including platforms that use magnetic beads conjugated to DNA aptamers and antibody-aptamer functionalized fiber-optic sensor for detection of L. monocytogenes cells from contaminated ready-to-eat meat products 29 . Hills et al 30 and Oliveira et al 31 reported a sensing mechanism for L. monocytogenes detection in food samples using the actuation of distinct chitosan-aptamer nanobrushes using the aptamer discovered by Ohk et al 29 . Recently, Sidhu et al 32 developed an aptasensor using platinum interdigitated microelectrodes functionalized with this same DNA aptamer for Listeria spp.…”
Section: Introductionmentioning
confidence: 99%